A simple new structural force field for the computation of linear metallocenes - Comba, Peter; Gyr, Thomas (European journal of inorganic chemistry, 1999)
A new structural force field for metallocenes is presented, which involves harmonic bonding potentials from the metal center to each of the carbon atoms, no angular potentials around the metal ion, inter-ligand 1,3-non-bonded interactions, and transferable parameters for the ligand backbones. The model has been parameterized for ferrocene, ruthenocene, and osmocene derivatives and the force field has been validated with relevant structures from the CSD files (Fe: 34, Ru: 10, Os: 2). The conformational space [rotation of the Cp (cyclopentadienyl) rings] has been searched with a cartesian stochastic search routine and energy barriers have been computed by scanning the pseudo-torsional angles involving the centroids of the two Cp rings. The computed energy barriers are smaller than those determined experimentally, but the predicted increase in transition energy upon substitution of the Cp rings is in agreement with experiment and the torsional angles for the minimum structures are computed accurately. It is suggested that the underestimated barrier height is due to the neglect of solvation.